Measuring the Effectiveness of Online and Face-to-Face Classes Using the Community of Inquiry Framework - Eric S Parilla (Education Policy and Development, 2024)
The research study aims to measure and compare the effectiveness of face-to-face and online classes in the context of the Community of Inquiry Framework consisting of cognitive presence, social presence and instructional presence. It uses mixed methods of research design, and the participants are faculty members and students of different universities and colleges all over the Philippines. The importance of this research study is it assessed the effectiveness of online and face-to-face classes using the Community of Inquiry framework.  Results showed that in all aspects of the Community of Inquiry Framework, the assessments of both modalities are highly effective. However, comparing the two modalities, FtF classes outweighed the online classes in all aspects. The 7 focus group discussions also yielded the same results, where students also identified 4 themes of advantages of the FtF modality which are; (1) Personal Interaction; (2) Real-Time Feedback; (3) Personalized Instruction; and (4) Reduced Distractions.